Studies in the Liocranidae (Araneae): revision of Andromma Simon, 1893 - Jocqué, Rudy; Bosselaers, Jan (European Journal of Taxonomy, 2022)
The genus Andromma Simon, 1893 is revised. The type species A. aethiopicum Simon, 1893 (♂♀) and the other three known species, A. anochetorum Simon, 1909 (♂), A. bouvieri Fage, 1936 (♀) and A. raffrayi Simon, 1899 (♂♀), are redescribed. The types of the subspecies A. raffrayi inhacorense Lessert, 1936 were not examined. This subspecies is considered a synonym of the nominal species. Nineteen new species are described and illustrated: A. albinovani sp. nov. (♂♀), A. alvoculatum sp. nov. (♀), A. anacardium sp. nov. (♀), A. cyamos sp. nov. (♀), A. cycnotrachelos sp. nov. (♂♀), A. delphiurum sp. nov. (♂♀), A. deogratias sp. nov. (♂♀), A. dicranobelos sp. nov. (♂), A. didrepanum sp. nov. (♂), A. divinagraciae sp. nov. (♂♀), A. elephantactes sp. nov. (♀), A. ghesquierei sp. nov. (♂♀), A. heligmos sp. nov. (♀), A. helix sp. nov. (♀), A. juakalyi sp. nov. (♂), A. katangensis sp. nov. (♀), A. ophiophagum sp. nov. (♀), A. prosopion sp. nov. (♀) and A. velum sp. nov. (♂♀). The distribution of the species and their apparent commensalism with termites are discussed.